Expression of galectin-1 in malignant tumors - Demydenko, D.; Berest, I. (Experimental Oncology, 2009)
Galectin-1 is a 14 kDa lectin expressed ubiquitously in mammalian organism. Since its discovery, the lectin was shown to participate in many cellular processes. Involvement in some of them like induction of apoptosis of activated T cells, mediation of cell adhesion and participation in angiogenesis suggest that galectin-1 could be utilized by malignant tumors. Indeed expression of galectin-1 is upregulated in tumors of different origin. Many examples point to its important role in a process of cancer metastasis. This review summarizes the data available to date on galectin-1 expression in human malignancies.